A Graphitic‐C3N4 "Seaweed" Architecture for Enhanced Hydrogen Evolution1. (15th July 2015) - Han, Qing; Wang, Bing; Zhao, Yang; Hu, Chuangang; Qu, Liangti
Abstract A seaweed‐like graphitic‐C3N4 (g‐C3N4 "seaweed") architecture has been prepared by direct calcination of the freeze‐drying‐assembled, hydrothermally treated dicyandiamide fiber network. The seaweed network of mesoporous g‐C3N4 nanofibers is favorable for light harvesting, charge separation and utilization of active sites, and has highly efficient photocatalytic behavior for water splitting. It exhibits a high hydrogen‐evolution rate of 9900 μmol h−1 g−1 (thirty times higher than that of its g‐C3N4 bulk counterpart), and a remarkable apparent quantum efficiency of 7.8 % at 420 nm, better than most of the g‐C3N4 nanostructures reported. This work presents a very simple method for designing and developing high‐performance catalysts for hydrogen evolution.